Polymer Nanocomposites Towards Multi-Functionality - Dasari, Aravind; Yu, Zhong-Zhen; Mai, Yiu-Wing (Engineering Materials and Processes, 2016)
This highlights ongoing research efforts on different aspects of polymer nanocomposites and explores their potentials to exhibit multi-functional properties. In this context, it addresses both fundamental and advanced concepts, while delineating the parameters and mechanisms responsible for these potentials. Aspects considered include embrittlement/toughness; wear/scratch behaviour; thermal stability and flame retardancy; barrier, electrical and thermal conductivity; and optical and magnetic properties. Further, the book was written as a coherent unit rather than a collection of chapters on different topics. As such, the results, analyses and discussions presented herein provide a guide for the development of a new class of multi-functional nanocomposites. Offering an invaluable resource for materials researchers and postgraduate students in the polymer composites field, they will also greatly benefit materials.